KONKRETISASI MAHASISWA PRAKTEK PENGALAMAN LAPANGAN (PPL) STIT IBNU RUSYD TANAH GROGOT DI MTs NEGERI 1 PASER - Adiyono Adiyono; Yulianti, Muhammad Azmi, Evy Fitriatun Nisa, Indah Savira Aurelita, Zulfa, Rahmawati (JOURNAL OF COMMUNITY DEDICATION, 2023)
This PPL activity is carried out through guided teaching practices carried out by STIT Ibnu Rusyd Tanah Grogot students at MTs 1 Paser for three months. Implemented by STIT Ibnu Rusyd Tanah Grogot students at MTs 1 Paser for three months. In its implementation, each students make learning tools and learning media in the form of in the form of Daily Activity Plans (RKH), Child Development Assessments, Analysis of Improvement and Enrichment and completing portfolios. Improvement and Enrichment and complete the child's portfolio. Students make educational media by considering several aspects and creative value, effective, efficient and interesting for children. The results achieved in Field Experience Practice activities involve two important things, namely classroom learning practices and making learning tools and learning media. The experiences that students have gained are expected to be new knowledge that can be applied later.